Mobility and participation among ageing powered wheelchair users: using a lifecourse approach. Issue 3 (24th March 2020) - Labbé, Delphine; Mortenson, W. Ben; Rushton, Paula W.; Demers, Louise; Miller, William C.
Abstract: About 65 million people use wheelchairs worldwide. Powered wheelchairs offer independent mobility for those who find it difficult to propel a manual wheelchair. Previous studies have described powered wheelchairs as a mixed blessing for the users in terms of usability, accessibility, safety, cost and stigma; however, few studies have explored their impact on mobility and participation over time. Therefore, as part of a larger longitudinal study, we used a combined retrospective and prospective lifecourse perspective to explore the experiences of older adult powered wheelchair users. Based on the interpretive description approach, 19 participants took part in a series of semi-structured interviews over a two-year period about their mobility, social participation and ageing process. The participants were powered wheelchair users, at least 50 years of age, recruited in Vancouver, Montreal and Quebec City (Canada). We identified three themes that highlighted how the powered wheelchair experience was integrated into the life continuum of the users. 'It's my legs' emphasised how powered wheelchairs are a form of mobility that not only enables users to take part in activities, but also impacts their identities, past and present. 'Wheels of change' explored the dynamic nature of powered wheelchair use and changes related to ageing. 'Getting around' illustrated how users' mobility was affected by the interaction with their physical and social environments. Developing public policies to advance social and environmental changes could help countries to ensure equity of access and social inclusion of those ageing with disabilities.